Expanding catalytic promiscuity of a bifunctional terpene synthase through a single mutation-induced change in hydrogen-bond network within the catalytic pocket - Xinye Wang; Yiyi Huang; Weiyan Zhang; Kangjie Lv; Xiaoying Li; Zhixin Wang; Li Zhang; Tom Hsiang; Lixin Zhang; Liming Ouyang; Xueting Liu (Synthetic and Systems Biotechnology, 2024)
Fungal bifunctional terpene synthases (BFTSs) catalyze the formation of numerous di-/sester-/tri-terpenes skeletons. However, the mechanism in controlling the cyclization pattern of terpene scaffolds is rarely deciphered for further application of tuning the catalytic promiscuity of terpene synthases for expanding the chemical space. In this study, we expanded the catalytic promiscuity of Fusarium oxysporum fusoxypene synthase (FoFS) by a single mutation at L89, leading to the production of three new sesterterpenes. Further computational analysis revealed that the reconstitution of the hydrogen-bond (H-bond) network of second-shell residues around the active site of FoFS influences the orientation of the aromatic residue W69 within the first-shell catalytic pocket. Thus, the dynamic orientation of W69 alters the carbocation transport, leading to the production of diverse ring system skeletons. These findings enhance our knowledge on understanding the molecular mechanisms, which could be applied on protein engineering terpene synthases on regulating the terpene skeletons.